Dose–Response Relationship Between Physical Activity and the Incidence of Peripheral Artery Disease in General Population: Insights From the National Health and Nutrition Examination Survey 1999–2004 - Qu, Cheng-Jia; Teng, Le-Qun; Liu, Xin-Nong; Zhang, Yong-Bao; Fang, Jie; Shen, Chen-Yang (Frontiers in Cardiovascular Medicine, 2021)
Abstract: Purpose: A low ABI ≦0.9 indicates peripheral artery disease (PAD) and physical activity (PA) represents an important non-surgical treatment for patients with PAD. However, as for the general population, the associations between PA, PAD and their mutual dependence are not well defined. Here we aimed to determine whether there is a dose-response relationship between PA and incidence of PAD in general population using restricted cubic spline (RCS). Patients and methods: This study analyzed 1370 adults aged ≧40 years who had participated in National Health and Nutrition Examination Survey (NHANES) during 1999-2004. Participants’ ABI were measured by trained technicians and PAD was defined as ABI≦0.9. PA was obtained with a standard questionnaire and metabolic equivalents (MET) were used to quantify the PA level. Logistic regression was used to assess the association between PA and incidence of PAD, and the dose-response relationship was analyzed with RCS. Results: PAD was present in 6.2% participants: 5.6% of males and 6.9% of females. After adjusting for potential confounders, compared with the first quartile (Q1) of MET, the odds ratios (ORs) of PAD for those with Q2, Q3 and Q4 of MET were 0.688 [95% confidence interval (CI)=0.684-0.692], 0.463 (95% CI=0.460-0.466), 0.816 (95% CI=0.812-0.821), respectively (all p<0.0001). The RCS regression showed that physical activity was related to the incidence of PAD in a non-linear manner (p for non-linearity<0.0001). For females, the prevalence of PAD decreased as physical activity increased, reaching the minimum for activity at approximately 5800 MET-min month-1 (OR=0.425, 95% CI=0.424-0.426), and for males, no pleatu was found in this study Conclusion: The prevalence of PAD is inversely associated with PA and vigorous activities might help decrease PAD risk for general population. The prevalence of PAD reaches the minimum at approximately 5800 MET-min month-1, representing a recommended PA value.